SIRI and SII as potential biomarkers of disease activity and lupus nephritis in systemic lupus erythematosus - Yang, Chi-Hui; Wang, Xin-Yi; Zhang, Yi-Hui; Ding, Ning (Frontiers in Immunology, 2025)
ObjectivesInflammation is important in the development of systemic lupus erythematosus (SLE). Systemic inflammation response index (SIRI) and systemic immune-inflammation index (SII) are novel clinical markers of inflammation with prognostic value in different diseases. However, the value of SIRI and SII as inflammation predictors in SLE remains unclear. This study explores the SIRI and SII as potential biomarkers for SLE.MethodsData from 280 individuals, including newly diagnosed SLE patients and healthy controls, were collected and divided into three groups: SLE without lupus nephritis (NLN) group (n=93), lupus nephritis (LN) group (n=96) and healthy control group (n=91). Differences in SIRI and SII among the three groups were compared. Logistic regression and Pearson linear analysis were used to analyze the predictive value and correlation of SIRI and SII with SLE and systemic lupus erythematosus disease activity index 2000 (SLEDAI-2K). Receiver operating characteristic (ROC) curves evaluated SIRI and SII in predicting SLE, SLE disease activity, and LN.ResultsThe SIRI and SII values were significantly higher in the LN group compared to the NLN group (p<0.01). SII had the largest area under the ROC curve for predicting LN (AUC: 0.6775, 95%CI: 0.6020 - 0.7531). Logistic regression analysis showed SIRI and SII as independent risk factors for LN. Pearson linear analysis indicated SIRI and SII were positively correlated with SLEDAI-2K (rSIRI=0.25, rSII=0.24, p<0.05).ConclusionsSIRI and SII are biomarkers of disease activity and renal involvement in SLE patients that can be used to evaluate and predict for SLE occurrence, disease activity, and lupus nephritis occurrence assessment.